0163 The Differential Relationship Between Berthing Habitability, Job Stress, and Workload on Self-Reported Sleep Deficiency in a Representative Sample of Sailors Attached to U.S. Navy Warships. (25th May 2022) - Kubala, Andrew; Jameson, Jason; Markwald, Rachel; Lai, Kevin; Roma, Peter; Russell, Dale
Abstract: Introduction: Berthing habitability factors (e.g., noise, temperature, lighting) and workload are known to negatively impact sleep for Sailors serving onboard United States (U.S.) Navy warships. However, it is unknown what factors have the strongest relationship with sleep outcomes. Using data from a representative sample of warships, the relationships between berthing habitability, job stress, and workload on sleep were explored. Methods: Participants (N = 3, 313; 84% ≤ 35 yrs, 55% white) from 33 warships voluntarily completed an online survey. Using structural equation modeling, latent factors of workload, job stress, and berthing habitability were modeled to test relationships with self-reported sleep deficiency. Sleep deficiency was calculated by dividing the sleep obtained on their ship ("How many hours of sleep (to include naps) per day do you get when sleeping onboard your current ship?") by their required sleep amount ("How many hours of sleep do you require to feel well-rested?"). Job stress was modeled with three scores from questions related to job stress (1=strongly disagree, 5=strongly agree). Habitability was modeled by the degree in which environmental factors disturbed sleep (1=not at all, 5=extremely). Workload was modeled by the hours completed performing job-related tasks (e.g., work center, watch team, training, meetings). Results: On average, participants reported shorter sleep durations on their ship than they require (Ship: 5.2±1.4 hrs; Required: 7.0±1.3 hrs, mean±SD). Overall, habitability, job stress, and workload were negatively related to sleep deficiency (standardized βs=-0.16 to -0.26, ps < 0.001, CFI/TLI > 0.90, RMSEA=0.056). Among all latent constructs, larger coefficients were found for the direct path from workload to sleep deficiency than those from habitability (β1=-0.16 vs β2=-0.12). Additionally, watch team duties loaded most heavily onto the construct of workload, suggesting that it contributed most to the relationship of workload with sleep deficiency. Conclusion: These results confirm that workload and berthing habitability are related to sleep deficiency in Sailors while serving onboard U.S. Navy Ships. Additionally, greater workload may have a stronger relationship with sleep deficiency than other factors such as habitability. Future research should utilize objective measures of sleep and workload to better estimate their relationships with sleep. Support (If Any): Military Operational Medicine Research Program (MOMRP) under work unit no. N2010.